2006
DOI: 10.4049/jimmunol.176.1.426
|View full text |Cite
|
Sign up to set email alerts
|

Internalizing Antibodies to the C-Type Lectins, L-SIGN and DC-SIGN, Inhibit Viral Glycoprotein Binding and Deliver Antigen to Human Dendritic Cells for the Induction of T Cell Responses

Abstract: The C-type lectin L-SIGN is expressed on liver and lymph node endothelial cells, where it serves as a receptor for a variety of carbohydrate ligands, including ICAM-3, Ebola, and HIV. To consider targeting liver/lymph node-specific ICAM-3-grabbing nonintegrin (L-SIGN) for therapeutic purposes in autoimmunity and infectious disease, we isolated and characterized Fabs that bind strongly to L-SIGN, but to a lesser degree or not at all to dendritic cell-specific ICAM-grabbing nonintegrin (DC-SIGN). Six Fabs with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 48 publications
2
33
0
Order By: Relevance
“…The expression of DC-SIGN is particularly well suited to ATV approaches as the receptor is expressed at high levels by multiple DC populations that can contribute to T-cell priming and activation. Similar to MR, DC-SIGN is an endocytic receptor that can mediate efficient antigen presentation through different ligands, and more recently using a novel humanized antibody, hD1 (Schjetne et al, 2002;Tacken et al, 2005;Dakappagari et al, 2006).…”
Section: Dc-sign Dc-specific Icam-grabbing Non-integrin (Dc-sign)mentioning
confidence: 99%
“…The expression of DC-SIGN is particularly well suited to ATV approaches as the receptor is expressed at high levels by multiple DC populations that can contribute to T-cell priming and activation. Similar to MR, DC-SIGN is an endocytic receptor that can mediate efficient antigen presentation through different ligands, and more recently using a novel humanized antibody, hD1 (Schjetne et al, 2002;Tacken et al, 2005;Dakappagari et al, 2006).…”
Section: Dc-sign Dc-specific Icam-grabbing Non-integrin (Dc-sign)mentioning
confidence: 99%
“…Most particularly, targeting antigens through the DC surface lectins DCIR [18,78], DC-SIGN [79], Dectin [80], Clec9A [81], and Langerin [82], results in humoral and/or cellular CD4 + and/or CD8 + T-cell responses. In the absence of adjuvants, targeting DEC205 + DCs in vivo can induce tolerance [75].…”
Section: Vaccination Via Dcs: In Vivo DC Targetingmentioning
confidence: 99%
“…The observation that DC-SIGN is effectively internalized by singlechain antibodies suggests that internalization is not dependent on receptor cross-linking, as is essential when targeting Fc receptors. [11][12][13] We previously demonstrated that ligand binding to the CRD of DC-SIGN results in clathrin-mediated internalization of the receptor and routing to late endosomal, LAMP-1, and MHC class II positive, compartments. 8,9,14,15 The observation of SierraFilardi et al, showing that antibodies recognizing the neck domain of DC-SIGN display an enhanced ability to trigger receptor internalization compared with CRD-binding antibodies, 16 prompted us to initiate a detailed study on antigen uptake and processing when targeting different epitopes of DC-SIGN.…”
Section: Introductionmentioning
confidence: 99%